2019
DOI: 10.1016/j.cortex.2019.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine effects on frontal cortical blood flow and motor inhibition in Parkinson's disease

Abstract: Parkinson's disease (PD) is characterized by dysfunction in frontal cortical and striatal networks that regulate action control. We investigated the pharmacological effect of dopamine agonist replacement therapy on frontal cortical activity and motor inhibition. Using Arterial Spin Labeling MRI, we examined 26 PD patients in the off-and on-dopamine agonist medication states to assess the effect of dopamine agonists on frontal cortical regional cerebral blood flow. Motor inhibition was measured by the Simon tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 108 publications
(121 reference statements)
5
11
0
Order By: Relevance
“…Furthermore, while previous studies focus on PD patients with and without ICB, we included analyses that self‐assess behavioral symptoms in a healthy cohort. Findings regarding increased motor impulsivity are less consistent, with some studies showing increased motor impulsivity in ICB patients, 15,61 There are no elevations in BIS‐11 motor impulsivity scores and this is consistent with previous studies that show intact behavioral motor inhibitory control in ICB patients 63‐65 and lower self‐reported ratings of motor impulsivity in PD patients with addictions 27 …”
Section: Discussionsupporting
confidence: 57%
“…Furthermore, while previous studies focus on PD patients with and without ICB, we included analyses that self‐assess behavioral symptoms in a healthy cohort. Findings regarding increased motor impulsivity are less consistent, with some studies showing increased motor impulsivity in ICB patients, 15,61 There are no elevations in BIS‐11 motor impulsivity scores and this is consistent with previous studies that show intact behavioral motor inhibitory control in ICB patients 63‐65 and lower self‐reported ratings of motor impulsivity in PD patients with addictions 27 …”
Section: Discussionsupporting
confidence: 57%
“…Previous studies suggested that PD was involved in the frontoparietal and frontostriatal network and showed cortical thinning of the middle and superior frontal areas and inferior parietal area on neuroimaging study. 15,16 Therefore, our findings are consistent with the results of these previous studies, because the rCBF of the frontal and parietal areas was changed.…”
Section: Discussionsupporting
confidence: 92%
“…Cerebral function was evaluated via changes in rCBF on cerebral perfusion SPECT, and the follow‐up images demonstrated significantly increased rCBF in the frontal medial and parietal areas when compared to baseline images. Previous studies suggested that PD was involved in the frontoparietal and frontostriatal network and showed cortical thinning of the middle and superior frontal areas and inferior parietal area on neuroimaging study . Therefore, our findings are consistent with the results of these previous studies, because the rCBF of the frontal and parietal areas was changed.…”
Section: Discussionsupporting
confidence: 92%
“…The prescribed target was identified according to standard techniques. To localize the DLPFC, we identified the mid-portion of the middle frontal gyrus along its longitudinal axis anterior to the pre-motor area (Trujillo et al, 2019), and designated this point as the midpoint for the subdural electrode. A radiopaque marker (18G needle) was placed at this point using the stereotactic headframe for localization.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…The DLPFC has direct connections to the STN (Haynes and Haber, 2013) and GPi (Middleton and Strick, 2002), as well as widespread connections to the caudate nucleus and to the orbitofrontal, cingulate, premotor, and pre-supplementary motor cortices (Ridderinkhof et al, 2004). In PD patients, functional magnetic resonance imaging (fMRI) studies reveal reduced DLPFC activity during inhibitory control tasks, with increased activity after administration of anti-Parkinsonian medications correlating to improved inhibitory control task performance (Trujillo et al, 2019). Furthermore, EEG studies show that theta-frequency activity is decreased in PD patients performing these tasks (Singh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%